Exchange Rate Volatility and its Impact on Industrial Production, Before and After the Introduction of Common Currency in Europe - Jamil, Muhammad; Streissler, Erich W.; Kunst, Robert M. (International Journal of Economics and Financial Issues, 2012)
We explored the impact of exchange rate volatility on industrial production before and after the introduction of common currency for eleven European countries included in European Monetary Union and for four European countries that did not adopt ‘Euro’ as common currency. Study employed monthly data of exchange rate and macroeconomic variables from January 1980 to April 2009 for the analysis. We employed AR(k)-EGARCH(p,q) models for calculation of volatility in growth rate of nominal and real exchange rates for all countries before and after the introduction of common currency separately. In this paper, we used Pooled IV/TSLS. We can conclude that all the countries enjoyed benefits after the introduction of common currency by reduction in negative impacts of real exchange rate volatility even some countries also faced increase in real exchange rate volatility. More than this, it can also be concluded that basket of fruits is not same for every country that joined common currency. Keywords: Common Currency; Euro; AR-EGARCH; Exchange Rate JEL Classification: F31; F36; F55; G31